(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
An interaction of chloride anionic complex of osmium (IV) with thiazine’s row organic basic dye dimethylthionine (Azure I) has been investigated. Forming ionic associate could be extracted by dichloroethan–tetrachlorocarbon (9 : 1) binary mixture. Maximal light absorption observed at 650 nm wavelengths. The optimal acidity of aqueous phase is pH 3.0 by hydrochloric acid. The optimal concentration of basic dye could be secured by the addition of 1.2–1.8 mL of 0.05% solution of dimethylthionine. The range of determined concentration is 2.5–56.6 mcg of Os (IV) in 10 mL of aqueous phase. The value of seeming coefficient of dimethylthionine hexachloroosmiate (IV) ionic associates organic extracts molar extinction ε(650) = 1.98 104 L· mol–1·cm–1. The molar ratio between dimethylthionine cation and hexachloroosmiate (IV) is 2 : 1.